Propozycja metody oceny efektywności dzielenia się wiedzą w przedsiębiorstwie - Sobieska-Karpińska, Jadwiga; Żmigrodzki, Marcin (The proposition of measurement method of knowledge sharing effectiveness in the enterprise, 2005)
The main aim of the article is to present an unusually deliberated problem, which is the measurement of knowledge sharing effectiveness. The paper contains also the model which includes costs and profits of knowledge sharing in an enterprise. The main elements of the model have been discussed. To simplify, it shows only the perspective of a single expert. The authors also show the realization of the proposed model in the selected enterprise, in which the knowledge management system has been implemented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 139-150